Labour markets and the crisis (Paris, 2010)
"The deep recession has led to a marked deterioration in labour market conditions in the OECD area. This paper, which draws heavily on other ongoing analytical work at the OECD, takes stock of recent labour market developments, highlights some of the key uncertainties in the early stages of the upturn, and discusses the policy options available to damp any further, structural deterioration in labour markets and facilitate an eventual, sustained, job-rich recovery."